Community Structure of Meiobenthos in Krueng Alue Sumirah, Samadua Subdistrict, south Aceh regency - Octavina, Chitra; Irfan, Muammar; Ulfah, Maria (Universitas Syiah Kuala, 2023)
This research was conducted to determine the communication structure of meibenthos in Krueng Alue Sumirah Waters, South Aceh Regency in February 2020. Determining the sampling location used the purposive sampling method for taking meiobenthos which was divided into upstream, middle and downstream rivers. The results showed the number of species found, namely, Gammarus sp., Cirolana, Diastylis sp. The upstream area of the river has the highest meiobenthos density than the middle and downstream areas. In addition, meiobenthos Gammarus sp. (0,0056 ind/m2) has the highest density than Cirolana (0,0028 ind/m2) and Diastylis sp. (0,0028 ind/m2) in the upstream area of the river with a diversity index value of 1.50 and a dominance value of 0.38, the meiobenthos distribution pattern that occurs is uniform and analysis of sediment grains in Krueng Alue Sumirah waters shows the type of gravel. Analysis of physico-chemical parameters showed that Krueng Alue Sumirah waters had a temperature ranging from 25 0C to 28 0C, current velocity was around 1.14 m/s, pH was 6.5 and DO was 5 mg/L. Overall the structure of the meiobenthos community in Krueng Alue Sumirah waters is classified as moderate for the biota in it.Keywords:Gammarus sp., Cirolana sp., Diastylis sp., Alue Sumirah, meiobenthos.